Sharing data, information, and software for the ESA Planck mission: the IDIS prototype - Bennett, Kevin; Bartelmann, Matthias (Advanced global communications technologies for astronomy, 2000)
During all phases of the Planck mission (Design, Development, Operations and Post-operations), it is necessary to guarantee proper information management among many Co-Is, Associates, engineers and technical and scientific staff (the estimated number of participants is over 200), located throughout countries in both Europe and North America. Information concerning the project ranges from instrument information (technical characteristics, reports, configuration control documents, drawings, public communications, etc.), to the analysis of the impact on science implied by specific technical choices. For this purpose, an Integrated Data and Information System (IDIS) will be developed to allow proper intra-Consortium and inter-Consortia information exchange. A set of tools will be provided, maximizing use of Commercial Off-The-Shelf (COTS) or reliable public domain software, to allow distributed collaborative research to be carried out. The general requirements for IDIS and its components have bene defined; the preparation of software requirements and COTS selection is being carried out. A prototype IDIS is expected to be available in spring 2000.